An Isoform-Selective Modulator of Cryptochrome 1 Regulates Circadian Rhythms in Mammals. Issue 9 (17th September 2020) - Miller, Simon; Aikawa, Yoshiki; Sugiyama, Akiko; Nagai, Yoshiko; Hara, Aya; Oshima, Tsuyoshi; Amaike, Kazuma; Kay, Steve A.; Itami, Kenichiro; Hirota, Tsuyoshi
Summary: Cryptochrome 1 (CRY1) and CRY2 are core regulators of the circadian clock, and the development of isoform-selective modulators is important for the elucidation of their redundant and distinct functions. Here, we report the identification and functional characterization of a small-molecule modulator of the mammalian circadian clock that selectively controls CRY1. Cell-based circadian chemical screening identified a thienopyrimidine derivative KL201 that lengthened the period of circadian rhythms in cells and tissues. Functional assays revealed stabilization of CRY1 but not CRY2 by KL201. A structure-activity relationship study of KL201 derivatives in combination with X-ray crystallography of the CRY1-KL201 complex uncovered critical sites and interactions required for CRY1 regulation. KL201 bound to CRY1 in overlap with FBXL3, a subunit of ubiquitin ligase complex, and the effect of KL201 was blunted by knockdown of FBXL3 . KL201 will facilitate isoform-selective regulation of CRY1 to accelerate chronobiology research and therapeutics against clock-related diseases. Graphical Abstract: Highlights: A phenotypic screen identifies KL201, a small-molecule circadian clock modulator KL201 stabilizes the clock protein CRY1 in an isoform-selective manner SAR study and X-ray crystallography reveal critical sites and interactions Effects of KL201 on CRY1 require FBXL3, a subunit of ubiquitin ligase complex Abstract : Miller et al. identified KL201 as an isoform-selective compound for the circadian clock protein CRY1. KL201 inhibits ubiquitin-dependent degradation of CRY1 and activates its transcriptional repressor activity, resulting in lengthening of the circadian period. KL201 will facilitate research on CRY1 isoform-selective functions and therapeutics against clock-related diseases.